The role of digital forensies in combating cybererimes - Harbawi, Malek; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2016)
The recent development in Information Communication Technology (ICT) has made changes in every aspect in our life. These changes are clearly reflected in cyberspace-related areas. The positive influence of cyberspace on knowledge, trade and business, and communication is undoubtable. However, there is a dark side of cyberspace deteriorates its peaceful usage that is cybercrimes. Cybercrimes are defined as any illegal activities practiced by or done via cyberspace and its electronic environment. Unlike "traditionalcrimes, cybercrimes present a real dilemma due to the fact that criminals' identity may be hidden or fraud in virtual domain. The concept of digital forensics have come to the existence in an attempt of formulating possible ways for cybercrimes investigation and analysis process. In this paper, we deplore the concept of digital forensics in the context of cybercrimes. An investigation of the positive impact of digital forensies in combating cybercrimes is discussed and useful remarks on open research issues are provided for further investigation activities. © 2016 IEEE.
4th International Symposium on Digital Forensics and Security, ISDFS 2016 -- 25 April 2016 through 27 April 2016 -- Little Rock -- 121690
Keywords: Cyber-attacks; Cybercrime; Digital forensics; Digital forensics tools, technology gap